Comparative study of the effect of long-term ageing on the behaviour of bitumen and mastics with mineral fillers. (20th November 2019) - Carl, C.; Lopes, P.; Sá da Costa, M.; Canon Falla, G.; Leischner, S.; Micaelo, R.
Highlights: Mastics stiffened to a lesser extent than bitumen with ageing treatment. The storage shear modulus proved to be more sensitive to the ageing and filler effect. Ageing had a minor effect on the specific energy of ductile fracture of mastics. Mastics with granite had lower fatigue resistance. Abstract: This study aims to evaluate the effect of mineral fillers on bitumen ageing. Two different bitumens and four mastics were investigated in the unaged and long-term aged states, based on different properties (consistency, rheology, fatigue resistance and ductility). Mastics stiffened less due to ageing treatment than bitumens, especially with granite filler. However, the results of the performance tests were not definitive regarding the effect of the filler. Aged bitumen showed greater fatigue resistance and higher specific energy of ductile fracture than unaged bitumen, whereas the mastics showed minor variations in the specific energy of ductile fracture with ageing treatment, which is indicative of less ageing, but the fatigue resistance decreased significantly in mastics with one of the bitumens.